(3GdeONd GdMOjK aj GbJUGOjGJ GdeGdjI GdYGeI (B/s - (3GdgjJj, fhRGO YHO GdQLefs; (3GdNTGdj, efLO YHO GddWjas ((3YeGf(B: s (3OGQ GdefGLL ddfTQ(B, s, 2005)
(3JYO GdeGdjI GdYGeI (B((3GbJUGOjGJ GdeGdjI GdYGeI(B) (3CMO GdYdhe GdGLJeGYjI GdMOjKI fSHjkG, aVdkG Yf chfg CMO aQhY Yde GdGbJUGO GdYGe hGdGbJUGO GdJWHjbj GdPj CNP jJWhQ ef MjK GdCOhGJ GdafjI hCSGdjH GdeYGdLI ddeSGFd GdNGUI HeGdjI GdMcheI, hGJSY fWGbg NdGd GdfUa GdKGfj ef GdbQf GdYTQjf NGUI YfO GJSGY fWGb eSDhdjI GdOhdI GLJeGYjkG hGfJbGAjkG(B. (3hbO COi gPG GdJWhQ Edi JWhjQ adSaI GdeGdjI GdYGeI ef eLQO chfg GdehVhY GdJbdjOj ddehGRfI Hjf GdEjQGOGJ GdYGeI hGdfabGJ GdYGeI, Edi chf gPG GdYde gh GfYcGS ddJMhdGJ GdGbJUGOjI hGdGLJeGYjI hGdSjGSjI GdJj CJSe HgG GdYUQ GdMOjK(B. (3hjHMK Yde GdeGdjI GdYGeI Ch eG jSei HGdGbJUGO GdeGdj aj JMbjb GdehGFeI Hjf eSJhi GdEjQGOGJ GdYGeI heSJhi GdfabGJ GdYGeI HeG jSge aj Md GdeTcdI GdGbJUGOjI, hGdESQGY aj JfajP GdeTGQjY GdEfeGFjI(B. (3hgcPG JYO GdeGdjI GdYGeI CMO GdCOhGJ GdegeI GdJj JSJNOegG GdOhdI aj GdfTGW GdGbJUGOj, aVdkG Yf chfgG ef Cge COhGJ GdJNWjW GdGbJUGOj HUaI YGeI hGdJNWjW GdeGdj HUaI NGUI(B. (3hdeG cGf GdGbJUGO GdeGdj jgJe HOQGSI CKQ GdeJZjQGJ GdeGdjI Ydi ELeGdj GdfTGW GdGbJUGOj aj GdeLJeY(B.s
(3HjHdjhZQGajG(B: (3U(B.177-182s
Keywords: (3GdGbJUGOs; (3GdeGdjI GdYGeIs; (3GdehGRfI GdYGeIs; (3GdfabGJ GdYGeIs